Educação de Jovens e Adultos: Identidades, Diários e Práticas no ensino de Bioquímica - Santos, Vanessa Freitas (2018)
This work made it possible to know the identity of students from the Youth and Adult Education (YAE) of a school in Itumbiara-Goiás, and to evaluate the use of a didactic sequence formulated from their experiences and learning desires using experimental practices to approach the content of Biochemistry. The classes developed with the students participating in this research were related to the Lipids concepts. The research was initiated by interviews with the students and the teacher, The research was initiated by interviews with the students and the teacher to know them like the research subjects and to understand their difficulties and expectations about teaching and learning in basic chemistry.. Later, a didactic sequence was developed that included the development of experimental activity: production of soap with used vegetable oil. The evaluation used in the research to collect and triangulate the data was the logbook, The evaluation used in the research to collect and triangulate the data was the logbook that made possible for the planning and reflection about this activities. It was possible This made possible to perceive the students' interests, motivation and learning with the experimental activity that it thematic is present in their daily lives. As a product of this dissertation, we constructed a Didactic Sequence with concepts of Biochemistry, which could be used by other fellow teachers.